In Pursuit of Diversity in Neighbourhoods: An Evaluation of Four Neighbourhoods in Famagusta - Saeidi, Sanaz (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: Since the beginning of Modernisation, there have been obvious shortcomings in planners‘ contribution to the concept of ―Diversity‖ in urban spaces. That is to say, many of the newly developed settlements specifically suburban developments have simply disregarded the significance of diversity in their physical, spatial, functional and socio-economic qualities as they became specialized zones of single use. Furthermore, lack of diversity in certain areas – mostly from the functional and socio-economic aspects – has caused considerable decline in their functionality that makes the inhabitants unable to meet their needs within the environment. Diversity among urban spaces refers to a wide range of issues – forms, uses and users – which together can bring variety of experiences and perceptual meanings attached to a particular area. This concept within the neighbourhood environments in terms of ―form‖ refers to variety of housing typologies, building (and other structural) forms and outdoor spaces (public, semi-public and private outdoor spaces) as well as natural elements; diversity of ―use‖ encompasses variety of facilities and services needed in residents‘ daily life – in a fine grained mixture – located within a reasonable distance of residential units. Thereupon, it can be assumed that a balanced mix of uses and facilities, well-arranged in a rich contextual pattern integrated with natural environment would benefit variety of users within the neighbourhood that is more likely to provide the environment with a condition which results in an effective communal life. This study focuses on the objective measures of diversity based on site analysis in four identical neighbourhoods of Famagusta, North Cyprus. As the same neighbourhoods were focused within a comprehensive user survey (―Famagusta Area Study‖, by Oktay, 2010) which determined the subjective measures of quality of life, this study will set out the possibilities for further explorations through comparing the objective and subjective measures, and finally seek out the possible impact of diversity on functionality of the neighbourhood environments. Keywords: Neighbourhood, diversity, objective measures, Famagusta neighbourhoods. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Modernizasyonun en başından beri kent plancılarının, kent mekanlarında çeşitlilik kavramının gelişmesine yeterli katkıları olmadığı görülmektedir. Daha açık bir deyişle, yeni gelişmekte olan yerleşimlerde, özellikle kent dışı konut alanlarında tek kullanımın egemen hale gelmesiyle çeşitlilik kavramının önemi fiziksel, mekansal, fonksiyonel ve sosyo-ekonomik olarak göz ardı edilmiştir. Ayrıca, çeşitliliğin hissedilemediği yerlerde, çoğunlukla fonksiyonel ve sosyo-ekonomik açıdan, insanların ihtiyaçlarını karşılayamamalarına neden olacak şekilde büyük bozulmalar yaşanmıştır. Kentsel alanlardaki çeşitlilik, (biçim, kullanım ve kullanıcılar olmak üzere) birçok konuyu kapsar. Bu çeşitlilik algısal deneyimde çeşitliliği ve bunun bir alana üç boyuttaki yansımasını sağlar.Çeşitlilik kavram, mahalle kapsamında, konut tipolojileri, bina (ve diğer yapısal) biçimleri ve dış mekanları (kamu, yarı kamu ve özel açık alanlar) ve doğal elemanlarla ilintilidir. Öte yandan kullanımların ve işlevlerin iyi dengelendiği bir çeşitlilik içinde insanlar pek çok yarar yanında daha iyi bir sosyal yaşama sahip olurlar. Bu çalışma Gazimağusa‘nın birbirinden farklı özelliklere sahip dört mahallesinde analizlere dayalı olarak yapılan objektif göstergelere yoğunlaşır. Söz konusu mahalleler, aynı zamanda daha önce gerçekleştirilen kapsamlı bir kullanıcı araştırmasında ―Gazimagusa Alan Çalışması, Oktay, 2010‖ öznel (subjektif) değerlendirmelerin yapıldığı alanlar olduğundan, nesnel (objektif) ve öznel (subjektif) değerlendirmelerin karşılaştırılarak, çeşitliliğin mahallenin işlevselliğine olası etkilerinin anlaşılmasına zemin hazırlayacaktır. Anahtar Sözcükler: Mahalleler, çeşitlilik, Nesnel (objektif) ölçüler, Gazimağusa mahalleleri.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2012. Supervisor: Prof. Dr. Derya Oktay.
Keywords: Architecture; Urban ecology (Sociology) - Neighbourhoods; Neighbourhood - Diversity - Objective Measures - Famagusta Neighbourhoods